2016
DOI: 10.17344/acsi.2015.1992
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic alkylation of acetone with ethanol over Pd/carbon catalyst in flow-through system via borrowing hydrogen route

Abstract: Consecutive alkylation of acetone with ethanol as model reactants was studied in order to obtain biomass based fuels by continuous processing of acetone-butanol-ethanol (ABE) mixture. Butanol, which can inevitably form as Guerbet side product in a self-aldol reaction of ethanol was not applied in our study as an initial component, in order to follow the complexity of the reaction mechanism. A flow-through reactor was applied with inert He or reducing H 2 stream in the temperature range of 150-350°C. Efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Onyestyak et al reported two closely related studies on the α-alkylation of acetone with ethanol in vapor phase using a fixed-bed reactor and two metal-based catalysts with a great potential for achieving C-alkylations, such as Pd and Cu. , …”
Section: Borrowing Hydrogen Methodology In Heterogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Onyestyak et al reported two closely related studies on the α-alkylation of acetone with ethanol in vapor phase using a fixed-bed reactor and two metal-based catalysts with a great potential for achieving C-alkylations, such as Pd and Cu. , …”
Section: Borrowing Hydrogen Methodology In Heterogeneous Catalystsmentioning
confidence: 99%
“…321 Onyestyak et al reported two closely related studies on the α-alkylation of acetone with ethanol in vapor phase using a fixed-bed reactor and two metal-based catalysts with a great potential for achieving C-alkylations, such as Pd and Cu. 322,323 In both cases, the authors moved from batch to a flowthrough system trying to get closer to the systems that are most frequently used in the industry. Although a priori these results are not easy to compare with those obtained in batch, the authors reached promising results.…”
Section: Activation Of Alcoholsmentioning
confidence: 99%
“…In our former [15][16][17] and the present works a commercial pelletized activated carbon (AC) (cylinders with 0.8 mm diameter and 2-4 mm length, Norit ROX 0.8 EXTRA, specific area: 1150 m 2 /g) as inert support was applied. The AC first was dried at 110°C, then impregnated with various alkaline compounds (lithium hydroxyde (LiOH), sodium hydroxyde (NaOH), potassium hydroxyde (KOH), cesium hydroxyde (CsOH), potassium phosphate K 3 PO 4 , calcium acetate Ca(Ac) 2 ), magnesium acetate (Mg(Ac) 2 ) and zinc acetate (Zn(Ac) 2 )) solutions using incipient wetness method and dried again at 110°C.…”
Section: Methodsmentioning
confidence: 99%
“…References [12,13] did not give specification about the used "5% palladium on carbon" catalysts. In our former studies, a commercial pelletized activated carbon (AC) (1150 m 2 /g) as inert support was applied [15][16][17]. The AC was impregnated with CsOH, KOH or K 3 PO 4 solutions using incipient wetness method and finally loaded with 5 m % palladium.…”
mentioning
confidence: 99%
See 1 more Smart Citation